Competition and Interhalogen Formation During Parallel Electrocatalytic Oxidation of Bromide and Chloride on Pt. Issue 4 (14th February 2020) - Vos, Johannes G.; Venugopal, Anirudh; Smith, Wilson A.; Koper, Marc T. M.
Abstract : Hydrogen production from seawater electrolysis is highly promising for the capture and storage of intermittent renewable energy, but is hindered by the possibility of unwanted reactions at the anode. The oxidation reactions of chloride and (to a lesser extent) bromide, which can occur in parallel to the evolution of oxygen, lead to environmentally harmful by-products and thus represent undesirable side-reactions. We present some general considerations of solution chemistry and oxidation products that may be expected in a mixed acidic bromide/chloride electrolyte. We performed electrochemical model studies of the simultaneous oxidation of bromide and chloride and their mutual interaction on a Pt electrocatalyst, with the aim of deepening the general understanding of the anodic competition problem. Using simplified model systems, our findings suggest that the oxidation of bromide is hindered by competing chloride adsorption, in a way that can be quite satisfactorily modelled by a simple Langmuir isotherm describing the competing adsorption and reactivity of all species. The oxidation of chloride was however not properly captured by this same model, and may be substantially different. Furthermore, the formation of the interhalogen compound BrCl seems to occur in-between the oxidation of bromide and chloride.